Game-theoretic differential evolution for multiobjective optimization of green sand mould system - Ganesan, T. (Springer Verlag, 2016)
Many large-scale engineering problems often take a multiobjective form. Thus, several solution options to the MO problem are usually ascertained by the engineer. Then the most desirable options with respect to the industrial circumstances and online operating conditions are selected. In this work, the trade-off solutions are obtained using the weighted-sum approach. In addition the standard metaheuristic, differential evolution is improved using concepts from evolutionary game theory. These techniques are then applied to solve the industrial green sand mould development problem. The solutions are then examined and discussed from various standpoints. Â© 2015, Springer-Verlag Berlin Heidelberg.